‘A Precarious Place': Housing and Clients of Specialized Courts - Quirouette, Marianne (The British journal of criminology, 2016)
Specialized courts rely on partnerships with community agencies to address multiple issues related to offending. Despite their popularity, little is known about the implications of such partnerships or about how stakeholders negotiate client support, therapeutic interventions and correctional practices. We analysed six Canadian sites (four drug treatment courts and two community/wellness courts), specifically focusing on how they conceptualize and respond to housing issues. We found that practices are pushing the boundaries of punishment and producing unintended consequences related to (1) positioning homelessness as criminogenic, (2) emphasizing short-term stability to the detriment of longer-term solutions and (3) facilitating enhanced supervision/knowledge exchange. When legal concerns dominate, therapeutic potential is compromised, along with efforts to restructure supports needed by marginalized offenders in the community.